Fabric waterproof agent and preparation method thereof
By combining the modified silica and low -containing fluorine -containing ribrite nuclear shell emulsion, the polyacryl acid waterproofing agent is solved when improving hydrophobic mechanical properties and safety and environmental protection issues, and the high durability and safety of fabrics and safety are realized. Environmental waterproofing agent.
Patent Information
- Application Number
- CN202410499228.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-24
- Publication Date
- 2025-01-28
AI Technical Summary
When existing polyacrylate textile waterproofing agents improve hydrophobicity, they can easily lead to degradation of mechanical properties, and the use of fluorine-containing components has safety and environmental protection problems.
The use of a modified silica is combined with a low -containing polyacryl -containing polyacrylate ribloniaculus emulsion to improve the waterproof performance of the fabric through the high decentralization of nano -titanium dioxide and the surface roughness of the modified silicon dioxide.
The high durability of the fabric is realized. At the same time, due to the low fluoride design, the waterproof agent is relatively safe and environmentally friendly.
Smart Images

Figure BDA0004808164700000111
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fabric waterproofing agents, and in particular to a fabric waterproofing agent and a preparation method thereof. Background Art
[0002] With the rapid development of science and technology and the improvement of living standards, people's functional requirements for textiles are also increasing, such as requiring textile products to be waterproof and oil-proof. Water-repellent finishing of textiles refers to reducing the surface energy of fibers through chemical finishing, giving fabrics dryness, waterproofness and other functions.
[0003] Among them, polyacrylate has excellent film-forming property, high gloss, good mechanical properties and ideal adhesion to a variety of substances, and is one of the most popular textile finishing agents. However, polyacrylate emulsions usually have low hydrophobicity. When waterproof performance is highly emphasized, it is necessary to change the composition or structure of the polyacrylate emulsion coating to improve its hydrophobicity. Many studies on hydrophobic coatings have focused on fluorine-modified polyacrylates. However, the use of fluorine-modified polyacrylates generally tends to lead to a decrease in the mechanical properties of polyacrylates, thereby reducing the durable waterproofness of waterproof fabrics. At the same time, if too much fluorine-containing components are added in the preparation of polyacrylic waterproofing agents, the waterproofing agents will be less safe and environmentally friendly due to the anti-degradation and toxicity of fluorine compounds. Summary of the invention
[0004] The purpose of the present invention is to provide a fabric waterproofing agent and a preparation method thereof. After the modified silica is combined with a low-fluorine-content polyacrylate core-shell emulsion, a waterproofing agent with excellent waterproof performance can be obtained, so that the waterproofed fabric has high durable waterproofness, and the waterproofing agent is relatively safe and environmentally friendly.
[0005] To achieve the above objectives, the present invention is implemented through the following technical solutions:
[0006] A fabric waterproofing agent comprises the following raw materials: polyacrylate core-shell emulsion and modified silicon dioxide; the weight ratio of the polyacrylate core-shell emulsion to the modified silicon dioxide is 100:2.5-3.8;
[0007] The polyacrylate core-shell emulsion comprises the following raw materials in parts by weight: 0.3-0.6 parts of nano titanium dioxide, 14-19 parts of a fluorine-free core monomer mixture, 10-15 parts of a fluorine-containing shell monomer mixture, 2-5 parts of an initiator aqueous solution for the fluorine-free core monomer mixture, 3-6 parts of an initiator aqueous solution for the fluorine-containing shell monomer mixture, 0.5-0.8 parts of an emulsifier, 0.05-0.2 parts of a chain transfer agent, and 70-100 parts of water.
[0008] Preferably, the fluorine-free core monomer mixture consists of methyl methacrylate, ethyl acrylate, octadecyl acrylate and hydroxyethyl methacrylate in a mass ratio of 10:3-4:2-3:2-3.
[0009] Preferably, the fluorine-containing shell monomer mixture is composed of methyl methacrylate, ethyl acrylate, octadecyl acrylate and trifluoroethyl methacrylate in a mass ratio of 10:4-5:2-3:3-4.
[0010] Preferably, the initiators in the aqueous initiator solution for the fluorine-free core monomer mixture are ammonium persulfate and azobisisobutylamidine hydrochloride, and the mass fractions of the ammonium persulfate and azobisisobutylamidine hydrochloride in the aqueous solution are 2-5% and 3-8%, respectively;
[0011] The initiators in the initiator aqueous solution for the fluorine-containing shell monomer mixture are ammonium persulfate and azobisisobutylamidine hydrochloride, and the mass fractions of the ammonium persulfate and azobisisobutylamidine hydrochloride in the aqueous solution are 3-6% and 5-9% respectively.
[0012] Preferably, the emulsifier is composed of octadecyl polyether acrylate trimethyl ammonium chloride and methacryloyloxyethyl dimethyl hexadecyl ammonium bromide in a mass ratio of 1:0.5-2; and the chain transfer agent is dodecyl mercaptan.
[0013] Preferably, the particle size of the nano titanium dioxide is 20-40 nm.
[0014] Preferably, the modified silicon dioxide comprises micron-sized silicon dioxide and nano-sized silicon dioxide supported on the micron-sized silicon dioxide; the particle size of the micron-sized silicon dioxide is 1-1.5 μm.
[0015] Preferably, the preparation method of the modified silicon dioxide comprises the following steps:
[0016] Add 1 part of micron-sized silicon dioxide to a mixture of 100 parts of ethanol and water, then drop 2.5-6 parts of ethyl orthosilicate ethanol solution and 1-1.5 parts of ammonia water while stirring, continue stirring for 5-6 hours after the addition is completed for 1-1.5 hours, then centrifuge, wash and dry to obtain the product.
[0017] Preferably, in the mixture of ethanol and water, the mass ratio of ethanol to water is 1:0.1-0.2; the mass fraction of ethyl orthosilicate in the ethyl orthosilicate ethanol solution is 20-25%; and the mass fraction of the ammonia water is 25-28%.
[0018] As a general inventive concept, the present invention provides a method for preparing a fabric waterproofing agent, comprising the following steps:
[0019] (1) adding nano titanium dioxide, an emulsifier, a chain transfer agent and 1 / 5-1 / 4 of a fluorine-free core monomer mixture to water, and using a cell crusher for ultrasonic emulsification to obtain a base liquid; heating the base liquid to 65-70° C., then adding an initiator aqueous solution for the fluorine-free core monomer mixture, and continuing to stir at a constant temperature for 1.5-2 hours to obtain a mixed liquid; simultaneously adding the remaining amount of the fluorine-free core monomer mixture dropwise to the mixed liquid, and completing the addition within 2-2.5 hours, and continuing to stir at a constant temperature for 1-1.5 hours to obtain a core emulsion;
[0020] (2) adding 3 / 5-4 / 5 of an aqueous solution of an initiator for a fluorinated shell monomer mixture to the core emulsion, and dripping the fluorinated shell monomer mixture, and after the dripping is completed within 2-2.5 hours, adding the remaining amount of the aqueous solution of an initiator for a fluorinated shell monomer mixture, and continuing the isothermal reaction for 2-2.5 hours to obtain a polyacrylate core-shell emulsion;
[0021] (3) Add modified silica to the polyacrylate core-shell emulsion, mix and stir for 30-60 minutes to obtain the product.
[0022] The technical effects of the present invention are:
[0023] The polyacrylate core-shell emulsion used for preparing the waterproofing agent of the present invention adopts a fluorine-free core monomer mixture composed of methyl methacrylate, ethyl acrylate, octadecyl acrylate and hydroxyethyl methacrylate to prepare the core, and adopts a fluorine-containing shell monomer mixture composed of methyl methacrylate, ethyl acrylate, octadecyl acrylate and trifluoroethyl methacrylate to prepare the shell, so that when the polyacrylate core-shell emulsion is used for waterproofing, the formed waterproof layer maintains high mechanical properties and has high durable waterproofness, and the polyacrylate core-shell emulsion contains only a small amount of fluorine-containing substances in the shell layer, and the fluorine-containing monomer is trifluoroethyl methacrylate, which has low toxicity. In addition, the core of the polyacrylate core-shell emulsion of the present invention contains nano titanium dioxide, which can make the nano titanium dioxide highly dispersed in the waterproofing agent, so that after being applied to fabric, the fabric can have a high self-cleaning effect, and the nano titanium dioxide can also improve the waterproofing performance of the waterproofing agent.
[0024] The modified silicon dioxide of the present invention includes micron-sized silicon dioxide (with a particle size of 1-1.5 μm) and nano silicon dioxide loaded on the surface thereof. The modified silicon dioxide has high surface roughness and dispersibility. After the modified silicon dioxide is used in combination with polyacrylate core-shell emulsion to prepare a waterproofing agent, the surface roughness of the fabric can be significantly improved, the water contact angle is further increased, and the hydrophobicity is stronger. The bonding force between the modified silicon dioxide with high surface roughness and the polyacrylate is higher, so that the fabric after waterproof finishing has higher durable waterproofness.
[0025] After the modified silicon dioxide of the present invention is combined with the polyacrylate core-shell emulsion with low fluorine content, a waterproofing agent with excellent waterproof performance can be obtained, so that the fabric after waterproofing treatment has high durable waterproofness, and the waterproofing agent is relatively safe and environmentally friendly. DETAILED DESCRIPTION
[0026] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] Embodiment 1:
[0028] A fabric waterproofing agent comprises the following raw materials: polyacrylate core-shell emulsion and modified silicon dioxide; the weight ratio of the polyacrylate core-shell emulsion and the modified silicon dioxide is 100:3.2.
[0029] The polyacrylate core-shell emulsion includes the following raw materials in parts by weight: 0.5 parts of nano titanium dioxide (particle size is 20-40nm), 16 parts of fluorine-free core monomer mixture, 15 parts of fluorine-containing shell monomer mixture, 3 parts of initiator aqueous solution for fluorine-free core monomer mixture, 5 parts of initiator aqueous solution for fluorine-containing shell monomer mixture, 0.5 parts of emulsifier, 0.1 parts of dodecyl mercaptan, and 80 parts of water.
[0030] The fluorine-free core monomer mixture is composed of methyl methacrylate, ethyl acrylate, octadecyl acrylate, and hydroxyethyl methacrylate in a mass ratio of 10:3:3:2. The fluorine-containing shell monomer mixture is composed of methyl methacrylate, ethyl acrylate, octadecyl acrylate, and trifluoroethyl methacrylate in a mass ratio of 10:5:3:3.
[0031] The initiators in the aqueous initiator solution for the fluorine-free core monomer mixture are ammonium persulfate and azobisisobutylamidine hydrochloride, and the mass fractions of ammonium persulfate and azobisisobutylamidine hydrochloride in the aqueous solution are 3% and 5%, respectively; the initiators in the aqueous initiator solution for the fluorine-containing shell monomer mixture are ammonium persulfate and azobisisobutylamidine hydrochloride, and the mass fractions of ammonium persulfate and azobisisobutylamidine hydrochloride in the aqueous solution are 5% and 9%, respectively.
[0032] The emulsifier is composed of octadecyl polyether acrylate trimethyl ammonium chloride and methacryloyloxyethyl dimethyl hexadecyl ammonium bromide in a mass ratio of 1:1.
[0033] The modified silicon dioxide includes micron-sized silicon dioxide and nano-sized silicon dioxide loaded on the micron-sized silicon dioxide; the particle size of the micron-sized silicon dioxide is 1-1.5 μm.
[0034] The preparation method of modified silicon dioxide comprises the following steps:
[0035] Add 1 part of micron-sized silicon dioxide to a mixture of 100 parts of ethanol and water (the mass ratio of ethanol to water is 1:0.2), then drop 6 parts of 25% by mass ethyl orthosilicate ethanol solution and 1.5 parts of 28% by mass ammonia water while stirring, continue stirring for 6 hours after the addition is completed for 1.5 hours, then centrifuge, wash and dry to obtain the product.
[0036] The preparation method of the above-mentioned fabric waterproofing agent comprises the following steps:
[0037] (1) adding nano titanium dioxide, an emulsifier, dodecyl mercaptan and 1 / 4 of a fluorine-free core monomer mixture to water, and using a cell crusher for ultrasonic emulsification to obtain a base liquid; heating the base liquid to 70° C., then adding an initiator aqueous solution for the fluorine-free core monomer mixture, and continuing to stir at a constant temperature for 2 hours to obtain a mixed liquid; simultaneously adding the remaining amount of the fluorine-free core monomer mixture dropwise to the mixed liquid, and completing the addition within 2 hours, and continuing to stir at a constant temperature for 1.5 hours to obtain a core emulsion;
[0038] (2) adding 4 / 5 of the aqueous initiator solution for the fluorinated shell monomer mixture to the core emulsion, and then dripping the fluorinated shell monomer mixture. After the dripping is completed within 2.5 hours, the remaining amount of the aqueous initiator solution for the fluorinated shell monomer mixture is added, and the reaction is continued at a constant temperature for 2 hours to obtain a polyacrylate core-shell emulsion;
[0039] (3) Add modified silica to the polyacrylate core-shell emulsion, mix and stir for 50 minutes to obtain the product.
[0040] Embodiment 2:
[0041] A fabric waterproofing agent comprises the following raw materials: polyacrylate core-shell emulsion and modified silicon dioxide; the weight ratio of the polyacrylate core-shell emulsion and the modified silicon dioxide is 100:2.5.
[0042] The polyacrylate core-shell emulsion includes the following raw materials in parts by weight: 0.3 parts of nano titanium dioxide (particle size is 20-40nm), 14 parts of fluorine-free core monomer mixture, 10 parts of fluorine-containing shell monomer mixture, 5 parts of initiator aqueous solution for fluorine-free core monomer mixture, 6 parts of initiator aqueous solution for fluorine-containing shell monomer mixture, 0.8 parts of emulsifier, 0.05 parts of dodecyl mercaptan, and 100 parts of water.
[0043] The fluorine-free core monomer mixture is composed of methyl methacrylate, ethyl acrylate, octadecyl acrylate, and hydroxyethyl methacrylate in a mass ratio of 10:4:2:2. The fluorine-containing shell monomer mixture is composed of methyl methacrylate, ethyl acrylate, octadecyl acrylate, and trifluoroethyl methacrylate in a mass ratio of 10:5:3:3.
[0044] The initiators in the aqueous initiator solution for the fluorine-free core monomer mixture are ammonium persulfate and azobisisobutylamidine hydrochloride, and the mass fractions of ammonium persulfate and azobisisobutylamidine hydrochloride in the aqueous solution are 2% and 8%, respectively; the initiators in the aqueous initiator solution for the fluorine-containing shell monomer mixture are ammonium persulfate and azobisisobutylamidine hydrochloride, and the mass fractions of ammonium persulfate and azobisisobutylamidine hydrochloride in the aqueous solution are 3% and 6%, respectively.
[0045] The emulsifier is composed of octadecyl polyether acrylate trimethyl ammonium chloride and methacryloyloxyethyl dimethyl hexadecyl ammonium bromide in a mass ratio of 1:0.5.
[0046] The modified silicon dioxide includes micron-sized silicon dioxide and nano-sized silicon dioxide loaded on the micron-sized silicon dioxide; the particle size of the micron-sized silicon dioxide is 1-1.5 μm.
[0047] The preparation method of modified silicon dioxide comprises the following steps:
[0048] Add 1 part of micron-sized silicon dioxide to a mixture of 100 parts of ethanol and water (the mass ratio of ethanol to water is 1:0.1), then drop 2.5 parts of 20% by mass ethyl orthosilicate ethanol solution and 1 part of 28% by mass ammonia water while stirring, continue stirring after the addition is completed for 1 hour, then centrifuge, wash and dry to obtain the product.
[0049] The preparation method of the above-mentioned fabric waterproofing agent comprises the following steps:
[0050] (1) adding nano titanium dioxide, an emulsifier, dodecyl mercaptan and 1 / 4 of a fluorine-free core monomer mixture to water, and using a cell crusher for ultrasonic emulsification to obtain a base liquid; heating the base liquid to 65° C., then adding an initiator aqueous solution for the fluorine-free core monomer mixture, and continuing to stir at a constant temperature for 1.5 hours to obtain a mixed liquid; simultaneously adding the remaining amount of the fluorine-free core monomer mixture dropwise to the mixed liquid, and completing the addition within 2 hours, and continuing to stir at a constant temperature for 1 hour to obtain a core emulsion;
[0051] (2) adding 3 / 5 of the aqueous initiator solution for the fluorinated shell monomer mixture to the core emulsion, and then dripping the fluorinated shell monomer mixture. After the dripping is completed within 2 hours, the remaining amount of the aqueous initiator solution for the fluorinated shell monomer mixture is added, and the reaction is continued at a constant temperature for 2.5 hours to obtain a polyacrylate core-shell emulsion;
[0052] (3) Add modified silica to the polyacrylate core-shell emulsion, mix and stir for 60 minutes to obtain the product.
[0053] Embodiment 3:
[0054] A fabric waterproofing agent comprises the following raw materials: polyacrylate core-shell emulsion and modified silicon dioxide; the weight ratio of the polyacrylate core-shell emulsion and the modified silicon dioxide is 100:3.8.
[0055] The polyacrylate core-shell emulsion includes the following raw materials in parts by weight: 0.6 parts of nano titanium dioxide (particle size is 20-40nm), 19 parts of fluorine-free core monomer mixture, 13 parts of fluorine-containing shell monomer mixture, 2 parts of initiator aqueous solution for fluorine-free core monomer mixture, 3 parts of initiator aqueous solution for fluorine-containing shell monomer mixture, 0.6 parts of emulsifier, 0.2 parts of dodecyl mercaptan, and 70 parts of water.
[0056] The fluorine-free core monomer mixture is composed of methyl methacrylate, ethyl acrylate, octadecyl acrylate, and hydroxyethyl methacrylate in a mass ratio of 10:3:2:3. The fluorine-containing shell monomer mixture is composed of methyl methacrylate, ethyl acrylate, octadecyl acrylate, and trifluoroethyl methacrylate in a mass ratio of 10:4:2:4.
[0057] The initiators in the aqueous initiator solution for the fluorine-free core monomer mixture are ammonium persulfate and azobisisobutylamidine hydrochloride, and the mass fractions of ammonium persulfate and azobisisobutylamidine hydrochloride in the aqueous solution are 5% and 3%, respectively; the initiators in the aqueous initiator solution for the fluorine-containing shell monomer mixture are ammonium persulfate and azobisisobutylamidine hydrochloride, and the mass fractions of ammonium persulfate and azobisisobutylamidine hydrochloride in the aqueous solution are 6% and 5%, respectively.
[0058] The emulsifier is composed of octadecyl polyether acrylate trimethyl ammonium chloride and methacryloyloxyethyl dimethyl hexadecyl ammonium bromide in a mass ratio of 1:2.
[0059] The modified silicon dioxide includes micron-sized silicon dioxide and nano-sized silicon dioxide loaded on the micron-sized silicon dioxide; the particle size of the micron-sized silicon dioxide is 1-1.5 μm.
[0060] The preparation method of modified silicon dioxide comprises the following steps:
[0061] Add 1 part of micron-sized silicon dioxide to a mixture of 100 parts of ethanol and water (the mass ratio of ethanol to water is 1:0.1), then drop 4 parts of 25% by mass ethyl orthosilicate ethanol solution and 1.2 parts of 28% by mass ammonia water while stirring, continue stirring for 6 hours after the addition is completed for 1.5 hours, then centrifuge, wash and dry to obtain the product.
[0062] The preparation method of the above-mentioned fabric waterproofing agent comprises the following steps:
[0063] (1) adding nano titanium dioxide, an emulsifier, dodecyl mercaptan and 1 / 5 of a fluorine-free core monomer mixture to water, and using a cell crusher for ultrasonic emulsification to obtain a base liquid; heating the base liquid to 65° C., then adding an initiator aqueous solution for the fluorine-free core monomer mixture, and continuing to stir at a constant temperature for 1.5 hours to obtain a mixed liquid; simultaneously adding the remaining amount of the fluorine-free core monomer mixture dropwise to the mixed liquid, and completing the addition within 2.5 hours, and continuing to stir at a constant temperature for 1 hour to obtain a core emulsion;
[0064] (2) adding 3 / 5 of the aqueous initiator solution for the fluorinated shell monomer mixture to the core emulsion, and then dripping the fluorinated shell monomer mixture. After the dripping is completed within 2 hours, the remaining amount of the aqueous initiator solution for the fluorinated shell monomer mixture is added, and the reaction is continued at a constant temperature for 2.5 hours to obtain a polyacrylate core-shell emulsion;
[0065] (3) Add modified silica to the polyacrylate core-shell emulsion, mix and stir for 30 minutes to obtain the product.
[0066] Embodiment 4:
[0067] A fabric waterproofing agent comprises the following raw materials: polyacrylate core-shell emulsion and modified silicon dioxide; the weight ratio of the polyacrylate core-shell emulsion to the modified silicon dioxide is 100:3.5.
[0068] The polyacrylate core-shell emulsion includes the following raw materials in parts by weight: 0.5 parts of nano titanium dioxide (particle size is 20-40nm), 15 parts of fluorine-free core monomer mixture, 10 parts of fluorine-containing shell monomer mixture, 3 parts of initiator aqueous solution for fluorine-free core monomer mixture, 5 parts of initiator aqueous solution for fluorine-containing shell monomer mixture, 0.5 parts of emulsifier, 0.15 parts of dodecyl mercaptan, and 100 parts of water.
[0069] The fluorine-free core monomer mixture is composed of methyl methacrylate, ethyl acrylate, octadecyl acrylate, and hydroxyethyl methacrylate in a mass ratio of 10:4:2:3. The fluorine-containing shell monomer mixture is composed of methyl methacrylate, ethyl acrylate, octadecyl acrylate, and trifluoroethyl methacrylate in a mass ratio of 10:5:2:3.
[0070] The initiators in the aqueous initiator solution for the fluorine-free core monomer mixture are ammonium persulfate and azobisisobutylamidine hydrochloride, and the mass fractions of ammonium persulfate and azobisisobutylamidine hydrochloride in the aqueous solution are 3% and 5%, respectively; the initiators in the aqueous initiator solution for the fluorine-containing shell monomer mixture are ammonium persulfate and azobisisobutylamidine hydrochloride, and the mass fractions of ammonium persulfate and azobisisobutylamidine hydrochloride in the aqueous solution are 6% and 5%, respectively.
[0071] The emulsifier is composed of octadecyl polyether acrylate trimethyl ammonium chloride and methacryloyloxyethyl dimethyl hexadecyl ammonium bromide in a mass ratio of 1:1.
[0072] The modified silicon dioxide includes micron-sized silicon dioxide and nano-sized silicon dioxide loaded on the micron-sized silicon dioxide; the particle size of the micron-sized silicon dioxide is 1-1.5 μm.
[0073] The preparation method of modified silicon dioxide comprises the following steps:
[0074] Add 1 part of micron-sized silicon dioxide to a mixture of 100 parts of ethanol and water (the mass ratio of ethanol to water is 1:0.15), then drop 5 parts of 22% by mass ethyl orthosilicate ethanol solution and 1.5 parts of 28% by mass ammonia water while stirring, continue stirring for 6 hours after the addition is completed for 1.5 hours, then centrifuge, wash and dry to obtain the product.
[0075] The preparation method of the above fabric waterproofing agent is the same as that of Example 1.
[0076] Embodiment 5:
[0077] A fabric waterproofing agent comprises the following raw materials: polyacrylate core-shell emulsion and modified silicon dioxide; the weight ratio of the polyacrylate core-shell emulsion and the modified silicon dioxide is 100:2.7.
[0078] The polyacrylate core-shell emulsion includes the following raw materials in parts by weight: 0.6 parts of nano titanium dioxide (particle size is 20-40nm), 16 parts of fluorine-free core monomer mixture, 12 parts of fluorine-containing shell monomer mixture, 3 parts of initiator aqueous solution for fluorine-free core monomer mixture, 3 parts of initiator aqueous solution for fluorine-containing shell monomer mixture, 0.5 parts of emulsifier, 0.05 parts of dodecyl mercaptan, and 80 parts of water.
[0079] The fluorine-free core monomer mixture is composed of methyl methacrylate, ethyl acrylate, octadecyl acrylate, and hydroxyethyl methacrylate in a mass ratio of 10:3:2:2. The fluorine-containing shell monomer mixture is composed of methyl methacrylate, ethyl acrylate, octadecyl acrylate, and trifluoroethyl methacrylate in a mass ratio of 10:5:2:3.
[0080] The initiators in the aqueous initiator solution for the fluorine-free core monomer mixture are ammonium persulfate and azobisisobutylamidine hydrochloride, and the mass fractions of ammonium persulfate and azobisisobutylamidine hydrochloride in the aqueous solution are 5% and 3%, respectively; the initiators in the aqueous initiator solution for the fluorine-containing shell monomer mixture are ammonium persulfate and azobisisobutylamidine hydrochloride, and the mass fractions of ammonium persulfate and azobisisobutylamidine hydrochloride in the aqueous solution are 6% and 6%, respectively.
[0081] The emulsifier is composed of octadecyl polyether acrylate trimethyl ammonium chloride and methacryloyloxyethyl dimethyl hexadecyl ammonium bromide in a mass ratio of 1:1.
[0082] The modified silicon dioxide includes micron-sized silicon dioxide and nano-sized silicon dioxide loaded on the micron-sized silicon dioxide; the particle size of the micron-sized silicon dioxide is 1-1.5 μm.
[0083] The preparation method of modified silicon dioxide comprises the following steps:
[0084] Add 1 part of micron-sized silicon dioxide to a mixture of 100 parts of ethanol and water (the mass ratio of ethanol to water is 1:0.1), then drop 3 parts of 25% by mass ethyl orthosilicate ethanol solution and 1.2 parts of 28% by mass ammonia water while stirring, continue stirring after 1.5 hours of addition, then centrifuge, wash and dry to obtain the product.
[0085] The preparation method of the above fabric waterproofing agent is the same as that of Example 2.
[0086] Comparative Example 1:
[0087] The difference from Example 5 is that the modified silicon dioxide is replaced by micron-sized silicon dioxide with a particle size of 1-1.5 μm.
[0088] Comparative Example 2:
[0089] The difference from Example 5 is that the modified silicon dioxide is replaced by nano silicon dioxide with a particle size of 30-50 nm.
[0090] Comparative Example 3:
[0091] The difference from Example 5 is that the fluorine-free core monomer mixture is replaced by a mixture of methyl methacrylate, ethyl acrylate, octadecyl acrylate, and trifluoroethyl methacrylate in a mass ratio of 10:5:2:3.
[0092] Performance Test:
[0093] The waterproofing agent was added with water to adjust the mass concentration to 80g / L, and then used for waterproof finishing of fabric, which was pure cotton bleached twill fabric. During finishing, the fabric was subjected to padding treatment, specifically two dips and two pads (the padding ratio was 75-80%), then dried at 75°C, and then placed at 160°C for 2 minutes.
[0094] The contact angle was tested according to AATCC22-2005 "Water Repellency Test: Spray Method". The color fastness to soaping was determined according to GB / T 3921.1-2008. The specific test results are shown in Table 1:
[0095] Table 1:
[0096]
[0097] As shown in Table 1, the waterproofing agent in the embodiment of the present invention is used to waterproof the fabric. Even after multiple washings, the fabric surface is still firmly loaded with a waterproof film layer, and the fabric has a higher hydrophobicity. As shown in Example 5 and Comparative Examples 1-2, compared with the use of unmodified micron-sized silica and nano-silicon dioxide, a better hydrophobic effect can be obtained by loading nano-sized silica on the surface of micron-sized silica, and the waterproof durability is stronger. In addition, as shown in Example 5 and Comparative Example 3, the present invention uses a fluorine-free nuclear monomer mixture to replace a fluorine-containing nuclear monomer mixture, which can improve the durable waterproofness without significantly reducing the hydrophobicity.
[0098] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A fabric waterproofing agent, characterized in that: The invention comprises the following raw materials: polyacrylate core-shell emulsion and modified silicon dioxide; the weight ratio of the polyacrylate core-shell emulsion and the modified silicon dioxide is 100:2.5-3.8; The polyacrylate core-shell emulsion comprises the following raw materials in parts by weight: 0.3-0.6 parts of nano titanium dioxide, 14-19 parts of a fluorine-free core monomer mixture, 10-15 parts of a fluorine-containing shell monomer mixture, 2-5 parts of an initiator aqueous solution for the fluorine-free core monomer mixture, 3-6 parts of an initiator aqueous solution for the fluorine-containing shell monomer mixture, 0.5-0.8 parts of an emulsifier, 0.05-0.2 parts of a chain transfer agent, and 70-100 parts of water.
2. The fabric waterproofing agent according to claim 1, characterized in that: The fluorine-free core monomer mixture is composed of methyl methacrylate, ethyl acrylate, octadecyl acrylate and hydroxyethyl methacrylate in a mass ratio of 10:3-4:2-3:2-3.
3. The fabric waterproofing agent according to claim 1, characterized in that: The fluorine-containing shell monomer mixture is composed of methyl methacrylate, ethyl acrylate, octadecyl acrylate and trifluoroethyl methacrylate in a mass ratio of 10:4-5:2-3:3-4.
4. The fabric waterproofing agent according to claim 1, characterized in that: The initiators in the aqueous initiator solution for the fluorine-free core monomer mixture are ammonium persulfate and azobisisobutylamidine hydrochloride, and the mass fractions of the ammonium persulfate and azobisisobutylamidine hydrochloride in the aqueous solution are 2-5% and 3-8% respectively; The initiators in the initiator aqueous solution for the fluorine-containing shell monomer mixture are ammonium persulfate and azobisisobutylamidine hydrochloride, and the mass fractions of the ammonium persulfate and azobisisobutylamidine hydrochloride in the aqueous solution are 3-6% and 5-9% respectively.
5. The fabric waterproofing agent according to claim 1, characterized in that: The emulsifier is composed of octadecyl polyether acrylate trimethyl ammonium chloride and methacryloyloxyethyl dimethyl hexadecyl ammonium bromide in a mass ratio of 1:0.5-2; and the chain transfer agent is dodecyl mercaptan.
6. The fabric waterproofing agent according to claim 1, characterized in that: The particle size of the nano titanium dioxide is 20-40nm.
7. The fabric waterproofing agent according to claim 1, characterized in that: The modified silicon dioxide comprises micron-sized silicon dioxide and nano silicon dioxide supported on the micron-sized silicon dioxide; the particle size of the micron-sized silicon dioxide is 1-1.5 μm.
8. The fabric waterproofing agent according to claim 7, characterized in that: The preparation method of the modified silicon dioxide comprises the following steps: Add 1 part of micron-sized silicon dioxide to a mixture of 100 parts of ethanol and water, then drop 2.5-6 parts of ethyl orthosilicate ethanol solution and 1-1.5 parts of ammonia water while stirring, continue stirring for 5-6 hours after the addition is completed for 1-1.5 hours, then centrifuge, wash and dry to obtain the product.
9. The fabric waterproofing agent according to claim 8, characterized in that: In the mixed solution of ethanol and water, the mass ratio of ethanol to water is 1:0.1-0.2; the mass fraction of ethyl orthosilicate in the ethyl orthosilicate ethanol solution is 20-25%; and the mass fraction of the ammonia water is 25-28%.
10. A method for preparing a fabric waterproofing agent as claimed in any one of claims 1 to 9, characterized in that: The following steps are involved: (1) adding nano titanium dioxide, an emulsifier, a chain transfer agent and 1 / 5-1 / 4 of a fluorine-free core monomer mixture to water, and using a cell crusher for ultrasonic emulsification to obtain a base liquid; heating the base liquid to 65-70° C., then adding an initiator aqueous solution for the fluorine-free core monomer mixture, and continuing to stir at a constant temperature for 1.5-2 hours to obtain a mixed liquid; simultaneously adding the remaining amount of the fluorine-free core monomer mixture dropwise to the mixed liquid, and completing the addition within 2-2.5 hours, and continuing to stir at a constant temperature for 1-1.5 hours to obtain a core emulsion; (2) adding 3 / 5-4 / 5 of an aqueous solution of an initiator for a fluorinated shell monomer mixture to the core emulsion, and dripping the fluorinated shell monomer mixture, and after the dripping is completed within 2-2.5 hours, adding the remaining amount of the aqueous solution of an initiator for a fluorinated shell monomer mixture, and continuing the isothermal reaction for 2-2.5 hours to obtain a polyacrylate core-shell emulsion; (3) Add modified silica to the polyacrylate core-shell emulsion, mix and stir for 30-60 minutes to obtain the product.